Comparative study of egg quality parameters of different breeds of peacock - Shakeela Khalid; Sana Ashraf; Sarfraz Khan; Waseem Khalid; Moses Vernonxious Madalitso Chamba (International Journal of Food Properties, 2023)
The current research work was conducted to compare the external and internal egg quality parameters of different breeds of peacock. For this purpose, 130 freshly laid eggs of 2 species and 11 breeds (n = 10 per breed) were obtained from captive breeding facilities. In Pavo muticus muticus, higher egg weight (106.57 ± 0.69), egg length (7.21 ± 0.01), egg width (5.31 ± 0.01), egg breadth (28.18 ± 0.01), and egg volume (100.84 ± 0.48) were recorded. However, higher egg shape index (80.16 ± 0.27) was noted in black shoulder, while higher egg surface area (263.8 ± 0.01) was found in Spalding purple. Significantly higher albumen diameter (11.02 ± 0.05), albumen weight (47.06 ± 0.24), albumen height (0.946 ± 0.02), albumen ratio (49.83 ± 0.13), yolk height (1.66 ± 0.01), yolk index (35.75 ± 0.13), and shell thickness (0.67 ± 0.00) were found in Pavo cristatus. Albumen pH (6.43 ± 0.01), yolk diameter (6.93 ± 0.04), yolk ratio (61.80 ± 0.87), and yolk weight (51.66 ± 0.34) were noted to be higher in Indian white. Higher shell weight (16.38 ± 0.42), shell ratio (17.004 ± 0.38), and Haugh unit (88.57 ± 0.84) were observed in Buford bronze pied. The study suggested that P.m. muticus and Pavo cristatus showed best external and internal egg quality traits as compared to other breeds. It further provided a reference and theoretical basis for artificial breeding, ecological protection, raising, and management of different breeds of peacocks.